Scattering of oblique water waves by an infinite step - Dolai, P.; Dolai, D.P. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper is concerned with the problem of scattering of obliquely incident surface water wave train passing over a step bottom between the regions of finite and infinite depth. Havelock expansions of water wave potentials are used in the mathematical analysis to obtain the physical parameters reflection and transmission coefficients in terms of integrals. Appropriate multi-term Galerkin approximations involving ultra spherical Gegenbauer polynomials are utilized to obtain very accurate numerical estimates for reflection and transmission coefficients. The numerical results are illustrated in tables.
Keywords: infinite step; Havelock expansion; Galerkin approximation; Gegenbauer polynomial; reflection coefficients; transmission coefficients